IMPLEMENTASI FSM (FINITE STATE MACHINE) PADA GAME MUSLIMS EXPLORER’S FAITHFUL MAZE ADVENTURE - Najah Muchsin Sanin (JASTEN (Jurnal Aplikasi Sains Teknologi Nasional), 2024)
The development of the gaming industry has undergone rapid transformation in the last few decades. In this context, the emphasis in game development is increasingly aimed at deeper and more complex player experiences. In response to these demands, Finite State Machines have become a popular and effective approach in creating organized storylines and better managing characters. By applying FSM to the game "Muslims Explorer's Faithful Maze Adventure" it can provide a more dynamic and structured game experience. This game is designed as a means of education and entertainment. Meanwhile, this article will review the basic concepts of FSM, describe its implementation in games, and highlight the use of FSM in improving the quality of the gaming experience.